Tahap Preliminary Research Pengembangan LKPD Matematika Berbasis Konstruktivisme Materi Program Linier - Rahma Oktaviani; Zulfah (Jurnal Inovasi Matematika, 2020)
This research intends to lead an initial analysis in developing students' worksheets (LKPD) based on constructivism to facilitate the students’ ability in understanding the mathematical concepts optimally. This research used the Borg and Gall Model which consists of ten stages, but in this study conducted the first stages, preliminary research stage. The first step is the initial stage of the research; it needed analysis, students’ analysis, curriculum analysis, construct analysis, and analysis of existing teaching materials. Based on the results of the preliminary analysis, it can be concluded that to be able to fortify students’ ability in understanding the mathematical concepts, the teachers need learning tools that will help students learn and expand their skills in understanding mathematical concepts in the linear program material. The students’ worksheet, which is based on one of the methods that have been shown to enhance the ability to understand concepts, namely Constructivism, should provide information that will help students improve the ability to understand their concepts.